Interventions to Prevent Women Developing Gestational Diabetes Mellitus: An Overview of Cochrane Reviews - Griffith, RJ; Alsweiler, J; Emoore, A; Brown, S; Middleton, P; Shepherd, E; Crowther, CA (Cochrane Collaboration, 2019)
This is a protocol for a Cochrane Review (Overview). The objectives are as follows: To summarise the evidence from Cochrane systematic reviews regarding the effects of interventions to prevent women developing gestational diabetes mellitus (GDM).